Economic Value of Coral Reef Ecosystem in Balikukup Island Batu Putih Sub-District Berau District (Jurnal Pembangunan Perikanan dan Agribisnis, 2015)
The purposed of the research is to analized economic value of coral reef ecosystem in Balikukup island based on fishing. Sample was taken with Purposive Sampling method than analyzed with Effect on Productivity (EOP). The results showed that the economic value of coral reef ecosystem in Balikukup island is Rp. 13.100.714/ha/year. It’s mean, if the coral reef ecosystem in Balikukup island demaged, the government disadvantage is Rp.13.100.714/ha/year.